2020
DOI: 10.1111/mcn.13088
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of breastfeeding during COVID‐19: Lessons for future practical and emotional support

Abstract: The COVID‐19 pandemic and subsequent lockdown and social distancing led to changes to breastfeeding support available to women in the United Kingdom. Face‐to‐face professional support was reduced, and face‐to‐face peer support was cancelled. Anecdotal media accounts highlighted practices separating some mothers and babies in hospitals, alongside inaccurate stories of the safety of breastfeeding circulating. Meanwhile, new families were confined to their homes, separated from families and support networks. Give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
368
3
27

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(413 citation statements)
references
References 44 publications
(54 reference statements)
15
368
3
27
Order By: Relevance
“…Although these problems were not directly related to COVID-19, their treatment was not conducted due to the pandemic [ 37 ]. The online survey by Brown and Shenker [ 13 ] conducted in the United Kingdom collected data from 1219 breastfeeding mothers (infants ≤ 12 months of age) and reported that although 18.9% ( n = 230) of the women surveyed stated to have stopped breastfeeding, this was due to other reasons unrelated to COVID-19. Although the majority of the sample was constituted by women who gave birth during the pandemic (59.4%; n = 724), the main reason presented for interrupting breastfeeding was the overall lack of professional support, regardless the time of birth (pre vs. during the pandemic).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although these problems were not directly related to COVID-19, their treatment was not conducted due to the pandemic [ 37 ]. The online survey by Brown and Shenker [ 13 ] conducted in the United Kingdom collected data from 1219 breastfeeding mothers (infants ≤ 12 months of age) and reported that although 18.9% ( n = 230) of the women surveyed stated to have stopped breastfeeding, this was due to other reasons unrelated to COVID-19. Although the majority of the sample was constituted by women who gave birth during the pandemic (59.4%; n = 724), the main reason presented for interrupting breastfeeding was the overall lack of professional support, regardless the time of birth (pre vs. during the pandemic).…”
Section: Resultsmentioning
confidence: 99%
“…The online survey by Brown and Shenker [ 13 ], showed that breastfeeding experiences were influenced by the COVID-19 pandemic, either positively (41.8%; e.g., spending more time at home, experiencing less social pressure, and fewer visitors), negatively (27%; e.g., less perceived support, worries about safety of breastfeeding, and isolation), or neutrally (29.5%). Women who perceived the breastfeeding experience during the pandemic as more challenging were less likely to describe themselves as ready to stop breastfeeding.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…• The measures to avoid transmission, such as prolonged lockdowns, increase the prevalence of depression and anxiety during early post-partum period (Brown & Shenker, 2020;Ceulemans, Hompes, & Foulon, 2020).…”
mentioning
confidence: 99%